Circulating liver function markers and the risk of COPD in the UK Biobank - Du, Wencong; Guan, Haoyu; Wan, Xinglin; Zhu, Zheng; Yu, Hao; Luo, Pengfei; Chen, Lulu; Su, Jian; Lu, Yan; Hang, Dong; Tao, Ran; Wu, Ming; et al. (Frontiers in Endocrinology, 2023)
Objective: To investigate the associations of circulating liver function marker levels with the risk of chronic obstructive pulmonary disease (COPD). Methods: We leveraged the data of 372,056 participants from the UK Biobank between 2006 and 2010. The assessed circulating liver function markers included alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), total bilirubin (TBIL), albumin (ALB), and total protein (TP). Incident COPD was identified through linkage to the national health service registries. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: During a median follow-up period of 12.3 (interquartile range:11.4-13.2) years, we documented 10,001 newly diagnosed COPD cases. Lower levels of ALT, TBIL, ALB, and TP and higher levels of GGT and ALP were nonlinearly associated with elevated COPD risk. The HR (95% CI) for decile 10 vs. 1 was 0.92 (0.84-1.01) for ALT, 0.82 (0.75-0.89) for TBIL, 0.74 (0.67-0.81) for ALB, 0.96 (0.88-1.04) for TP, 1.45 (1.31-1.62) for GGT, and 1.31 (1.19-1.45) for ALP. Restricted cubic spline analyses suggested a U-shaped relationship between AST levels and COPD risk (P for nonlinearity <0.05). Conclusion: We observed that all seven circulating liver function markers were nonlinearly associated with the risk of COPD, indicating the importance of liver function in COPD.